The Effects of Hand Exercise on Function and Physical Impairments in Patient with Hand Osteoarthritis - Majid Farhadian; Zahra Morovati; Alireza Shamsoddini; Hossein Akbari-Aghdam; Farzaneh Saberi (مجله دانشکده پزشکی اصفهان, 2018)
Background: Hand osteoarthritis is one of the most prevalent joint diseases and one of factors that cause disability in older adults. The present study aimed to investigate the effects of hand exercise on function and physical impairments in patient with hand osteoarthritis.